[3, 3]‐Sigmatropic Rearrangements of Naphthyl 1‐Propargyl Ethers: para‐Propargylation and Catalytic Asymmetric Dearomatization. (29th November 2022) - Wang, Lifeng; Zhou, Yuqiao; Su, Zhishan; Zhang, Fengcai; Cao, Weidi; Liu, Xiaohua; Feng, Xiaoming
Abstract: The para ‐Claisen rearrangement of aryl 1‐propargyl ethers involves two‐step [3, 3]‐sigmatropic rearrangements and dearomatization process, which has high activation barriers and is of challenge. Here we discovered thermal para ‐Claisen rearrangement of naphthyl 1‐propargyl ethers, and it enabled the formation of formal para ‐C−H propargylation products upon rearomatization. Chirality transfer occurred if optically active propargyl ethers were employed, leading to the construction of aryl/propargyl‐containing stereogenic centers. Moreover, catalytic asymmetric dearomatization of naphthyl 1‐propargyl ethers with different substitution at para ‐position gave access to benzocyclohexenones bearing all‐carbon quaternary stereocenters. The reaction was accelerated by a chiral N, N′ ‐dioxide/Co(OTf)2 complex catalyst to achieve high yields (up to 98 %) and high enantioselectivities (up to 93 % ee ). The DFT calculations and experimental results provided important clues to clarify the para ‐Claisen rearrangement process as well as the chiral induction and remote delivery. Abstract : The formal thermal para ‐C(sp 2 )−H propargylation of C4‐unsubstituted naphthyl 1‐propargyl ethers through para‐ Claisen rearrangement was described, and chirality transfer was observed. Moreover, the enantioselective dearomatization of C4‐substituted ones was realized by using a chiral N, N′ ‐dioxide/Co II complex catalyst. The DFT calculations and experimental results support the ortho ‐Claisen rearrangement/Cope rearrangement sequence process.